Design, synthesis and antitubercular evaluation of benzothiazinones containing an oximido or amino nitrogen heterocycle moiety. Issue 3 (5th January 2017) - Zhang, Rui; Lv, Kai; Wang, Bin; Li, Linhu; Wang, Bo; Liu, Mingliang; Guo, Huiyuan; Wang, Apeng; Lu, Yu
Abstract : A series of 8-nitro-6-(trifluoromethyl)-1, 3-benzothiazin-4-ones (BTZs) bearing an oximido or amino nitrogen heterocycle moiety through modifications at the C-2 position ofBTZ043 andBPTZ169 were designed and synthesized as new antitubercular agents. Abstract : A series of 8-nitro-6-(trifluoromethyl)-1, 3-benzothiazin-4-ones (BTZs) bearing an oximido or amino nitrogen heterocycle moiety through modifications at the C-2 position ofBTZ043 andBPTZ169 were designed and synthesized as new antitubercular agents. Many of the target compounds demonstrate excellent in vitro activity (MIC: <0.016–0.088 μg mL −1 ) against the drug susceptive H37Rv strain and two clinically isolated multidrug-resistant Mycobacterium tuberculosis (MTB) strains. Compound10a displays acceptable safety, aqueous solubility and pharmacokinetic properties, opening up a new possibility for further development.